See graph below
Step-by-step explanation:
![\begin{gathered} \text{Given: } \\ y\text{ = -4x + 3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/lj7m3r57kyvtkasjx1at8hdb3ehzsenfo7.png)
To graph the equation, we will assign values to x. Then we will get the corresponding values of y
let x = -2, -1, 0, 1, 2
when x = -2
y = -4(-2) + 3 = 11
when x = -1
y = -4(-1) + 3 = 7
when x = 0
y = -4(0) + 3 = 3
when x = 1
y = -4(1) + 3 = -1
when x = 2
y =-4(2) + 3 = -5
plotting the points: